Pátio do Poente - centro comercial e coworking - Milesi, Thaise Vieira (2022)
The main idea is to provide a commercial and office environment that is also interactive, connecting the public to entrepreneurs, in order to enhance the economic sector of the city and make it a reference in the region. Returning the potential of the place, and stimulating the permanence of visitors while making it a pleasant space for those who come to work there.